Determinants of VIA Screening Utilization: A Cross-Sectional Logistic Regression Study in an Archipelagic Setting of Eastern Indonesia - Rumaketty, Lidya; Moedjiono, Apik Indarty; Masni; Syam, Aminuddin; Riskiyani, Shanti; Yahya (International Journal of Statistics in Medical Research, 2026)
Background: Cervical cancer remains a leading cause of morbidity and mortality among women in low- and middle-income countries. Visual Inspection with Acetic Acid (VIA) is recommended as an effective and affordable screening method; however, coverage remains low in archipelagic regions of Eastern Indonesia. Objective: To examine the association between reproductive factors and contraceptive use with VIA screening utilization among women of reproductive age. Methods: A cross-sectional study was conducted among 131 women at a primary healthcare center in Ambon City. Data were analyzed using chi-square tests and multivariable logistic regression to estimate crude and adjusted odds ratios. Variables with p < 0.25 were included in the multivariable model. Model fit was assessed using the Hosmer–Lemeshow test, and explanatory power using Nagelkerke R². Results: A total of 65.6% of respondents had undergone VIA screening. No variables were significantly associated with screening utilization (p > 0.05). Contraceptive use showed a non-significant tendency toward increased screening likelihood (AOR = 1.837; 95% CI: 0.443–7.610). The model demonstrated weak explanatory power (Nagelkerke R² = 0.05), and the omnibus test was not statistically significant (p > 0.05), indicating limited predictive capacity. Conclusion: The study did not identify significant predictors of VIA utilization. The findings suggest that the variables included in the model were insufficient to explain screening behavior. Further studies with larger samples and more comprehensive analytical models are needed.